Cute dogs to needle felt : 6 pedigree pooches to make in simple steps - Button, Gai (Search Press, 2023)
"Using different wools, silks and fibres, and with just three needles, you can make all manner of realistic-looking dog breeds, including labradors, pugs and poodles. There are six dog projects in this book, and the techniques for making them are explained clearly with illustrated step-by-step instructions, along with handy tips. Each dog also has to-scale templates included, so you can start needle felting your favorite pooch right away. These beautiful dogs are easier to make than they look, making them suitable for beginners and confident felters alike!"--